DECISION SUPPORT SYSTEM FOR SELECTING DOCTORS IN APPLICATION X USING ANALYTICAL HIERARCHY PROCESS (AHP) - Teh Yu Ka; Wahyu Tisno Atmojo (Informatika, Universitas Jenderal Soedirman, 2022)
Doctors are one of the human resources contributing to the world of health, especially in the current COVID-19 pandemic situation. With the pandemic and increasing technological developments, this sat have sprung up many digital-based health service applications that can help the community, especially its users in health consultations, looking for health articles, and hospital searches. In this digital-based health service, if you want to consult online or make an appointment, there are many choices of doctors available with various criteria. This method is used to obtain weighting (Eigen Vector) criteria used to facilitate making decisions, which is to choose a doctor for consultation or appointment. With three criteria (experience, consultation price, and user satisfaction level) and alternatives (Dr. A, Dr. B, Dr. C) obtained weighting (Eigen Vector) or the best alternative option is Dr. A with a weighting value of 0.509, which has 27 years of experience criteria, a consultation price of Rp. 30,000.00, and a user satisfaction rate of 96%.